CLINICAL COURSE OF THE PREVALENCE OF DENTAL CARIES AND THE STATE OF PERIODONTAL TISSUE IN CHILDREN WITH RHEUMATISM - Sadieva D.Sh. (Scholar Express Journals, 2023)
Dental health is an important problem of childhood in all countries of the world. Periodontal diseases and dental caries are accompanied by complex morphofunctional changes in tissues. Therefore, early diagnosis of periodontal diseases, enamel demineralization and timely treatment, taking into account the age-related features of the periodontal structure in children, are of great importance. Rheumatism in children is an acute disease of an infectious-allergic nature. Symptoms of childhood rheumatism are most often detected in children aged 6 to 14 years.
Keywords: Dentistry; Rheumatism; Periodontium